Regional integration and development - Schiff, Maurice W.; Winters, L. Alan. (Washington, DC : World Bank ; [s.l.] : Oxford University Press, 2003)
Examines regionalism from the perspective of developing countries and presents a comprehensive account of existing theory and empirical results. It also incorporates the findings of formal analyses of the politics and dynamics of regionalism. It considers the relationship between regionalism and multilateralism and explores the economic advantages of nondiscriminatory trade liberalization, which the authors argue should be exploited to the maximum extent.
Includes bibliographical references (p. 271-297) and index.
oif 10/08/15; 21/08/15; 08/08/16
Loan
Keywords: International economic relations; Trade blocs; Regionalism; Commercial policy; Free trade